ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA UMKM DI DESA KARE, KABUPATEN MADIUN - Hasna Shafira Maghfiroh (Peneliti.net, 2023)
Micro, Small and Medium Enterprises (MSMEs) are one of the backbones of the country's economy. However, in the era of informational economic development which is increasingly massive, it must be admitted that efforts to continue to encourage the development of MSMEs are certainly not free from problems. This study aims to examine the effect of the field of business, education level, length of business, number of employees, and annual income on the performance of MSMEs in Kare Village, Madiun Regency. The causality approach is used to test whether there is a causal relationship between the independent variables and the determined dependent variable so that the phenomena that occur in the field based on the relationship between the independent variables and their effects can be explained. This study takes independent variables including financial management, education level, business sustainability, marketing techniques, and capital capabilities. While the dependent variable is the performance of SMEs. The sample used in this study were 61 SMEs registered in Kare Village. The data was obtained by distributing questionnaires to 61 MSME actors. The data analysis technique used is the Statistical Package for the Social Sciences (SPSS). Answers are obtained in the form of a Likert scale for each variable. The results of this study indicate that financial management, education level, business sustainability, marketing techniques, and capital capabilities comprehensively affect the performance of SMEs in Kare village.